IPO market timing with uncertain aftermarket retail demand - Santos, Francisco (Journal of Corporate Finance, 2017)
We develop a simple model of IPO timing with uncertain aftermarket retail demand. Firms prefer to go public when they expect to exploit sentiment-driven investors' overvaluations by setting offer prices above fundamental value. However, some firms have profitable investment opportunities that require immediate financing. This generates two empirical predictions: (i) the quality of the issuers' investments and (ii) their long-run performance decrease with expected retail demand. Using average IPO first-day returns as a proxy for retail demand, we find strong empirical support for the model. First, following the IPO, issuers in low-underpricing periods become more profitable and have higher investment rates than their peers. In contrast, issuers in high-underpricing periods have similar investment rates as their control firms, but become less profitable. Second, issuers in high-underpricing periods tend to underperform in the long-run, while issuers in low-underpricing periods do not.